Adolescents' reproductive health in north coastal line West Java: perceptions of adults - Juariah Juariah (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
PurposeThe aims of this study were to explore adults’ perceptions of issues related to adolescents reproductive health in North Coastal line of West Java, difficulty experiences of adults to help adolescents in dealing with their reproductive health problems and also perceptions of adults about solutions for adolescents reproductive health problems.MethodThis qualitative study was be done in Pusakajaya, Subang District, West Java Province. Number of informants were 45 adults people. They were teachers, parents and community leaders. Focus Group Discussion and Indepth Interview provided data for the content analysis. ResultsThis study showed that the mayor problems of adolescents reproductive health in this community were unintended pregnancy for the girls and smoking and substance misuse for the boys. The adults had some difficulties in interaction with adolescents. The teens preferred to make peers as their role models was an impediment. Troubles in adult-adolescent communication also accured. Teachers had diversity providing information on reproductive health due to the limitations of reference in the curriculum, materials and teaching aids. Poverty, residential environment of the adolescents, less attention from the local government were some barriers and challenges impacting adolescent reproductive health. Strengthening the family, increasing the schools capacity to give reproductive health information, continuous sensitization that supported by government regulation were identified by the informants as solutions in facing adolescent reproductive health problems. ConclusionInvolving adults to find the issues of adolescent reproductive health provide an overview of adolescent reproductive health, difficulty in dealing with adolescents and solutions that can be done to solve the problem of adolescent reproductive health